Multi-Omics Approaches: The Key to Improving Respiratory Health in People With Cystic Fibrosis? - Lee, Andrew J.; Einarsson, Gisli G.; Gilpin, Deirdre F.; Tunney, Michael M. (Frontiers in Pharmacology, 2020)
The advent of high-throughput multi-omics technologies has underpinned the expansion in lung microbiome research, increasing our understanding of the nature, complexity and significance of the polymicrobial communities harboured by people with CF (PWCF). Having established that structurally complex microbial communities exist within the airways, the focus of recent research has now widened to investigating the function and dynamics of the resident microbiota during disease as well as in health. With further refinement, multi-omics approaches present the opportunity to untangle the complex interplay between microbe–microbe and microbe–host interactions in the lung and the relationship with respiratory disease progression, offering invaluable opportunities to discover new therapeutic approaches for our management of airway infection in CF.